The correlates of nationalism in Beijing public opinion, 1998-2002 - Alastair Iain, Johnston (2016)
It is conventional wisdom in academic, policy and media analysis of post-June 4th China that Chinese nationalism is on the rise. This rather blunt conclusion comes mainly from anecdotal or unsystematically collected evidence, and it has not been subject to any rigorous testing. Drawing from the Beijing Area Study, an annual, randomly sampled survey of Beijing residents, this working paper examines in a preliminary fashion a subset of survey responses from 2000 to 2002 that tap into nationalist sentiment. The working paper finds that respondents who are in the middle class, who have some university education, or who have traveled abroad tend to hold less nationalistic attitudes than those who are poorer, less educated or who have not traveled abroad. Moreover, there is no evidence that those who 'came of age' politically in the post-June 4th period are more nationalistic than older political generations.